Analisis Pengaruh Sistem Informasi Akuntansi Terhadap Kinerja Usaha Mikro, Kecil dan Menengah (UMKM) di Desa Jatisari, Kecamatan Pakisaji, Kabupaten Malang - Trisnawati, Trisnawati; Maslichah, Maslichah; Mahsuni, Abdul Wahid (Universitas Islam Malang, 2023)
The purpose of this study was to examine about the influence of accounting information system on performance of micro, small and medium enterprises (MSMEs) in Jatisari Village, pakisaji District, Malang Regency. This type of research is qualitative correlational. The population in this study were Micro, Small and Medium Enterprises (MSMEs) in Jatisari Village, pakisaji District, Malang Regency. The sample in this study were 112 respondents from Jatisari Village who were taken using a purposive sampling technique. The data analysis method in this study is to use simple linear regression analysis and use several types of tests such as validity tests, reliability tests, normality tests and hypothesis tests consisting of simultaneous tests (F), coefficient of determination tests (R2) and partial tests (t). the results of this study indicate that partially the accounting information system variable has a positive and significant effect on performance of micro, small and medium enterprises (MSMEs) and simultaneously the accounting information system variable has a positive and significant effect on performance in micro, small and medium enterprises (MSMEs).Keywords : Accounting Information System, Performance of Micro, Small and Medium Enterprises (MSMEs)